Neck-tongue syndrome on sudden turning of the head. Issue 2 (February 1980) - Lance, J W; Anthony, M
Abstract : A syndrome of unilateral upper nuchal or occipital pain, with or without numbness in these areas, accompanied by simultaneous ipsilateral numbness of the tongue is explicable by compression of the second cervical root in the atlantoaxial space on sharp rotation of the neck. Afferents fibres from the lingual nerve travelling via the hypoglossal nerve to the second cervical root provide a plausible anatomical explanation for compression of that root causing numbness of half the tongue.